Un nuovo complesso episcopale nel Corno d'Africa di età tardo antica?: Gli scavi del Pontificio Istituto di Archeologia Cristiana ad Adulis (Eritrea) : 2018-2020 - Castiglia, Gabriele (Mitteilungen zur christlichen Archäologie, 2021)
Since 2018 the Pontificio Istituto di Archeologia Cristiana (Rome) is in charge of the excavation of one of the churches of the Aksumite town of Adulis, in the Red Sea coastline, in present day Eritrea. The aim of this paper is to present the new archaeological data coming from the recent excavations in the so-called "Church of the British Museum", discovered in 1868 by Captain Goodfellow. New excavations run from 2018 onwards have led to highlight the biggest church known so far in Adulis, probably the ecclesia episcopalis. It stands as a 30 meters long building, which follows the typical Aksumite architectural layout. Also, the great quantity of decorated marbles coming from the church are of great interest, revealing important contacts with Yemen and Byzantium, mostly in the 6th century. The new archaeological data will be contextualized in the wider scenario of the rise and establishment of early Christianity in the Aksumite kingdom.